The effect of KIA’s rebranding on consumer’s perceptions of brand image. - de Villiers, Lucile (The IIE, 2022)
In an era where innovation and progression prevail, consumers look towards brands who make a conscious effort to integrate their values and brand identity into the changing preferences of their consumers. KIA has attempted to illustrate their future focused vision by implementing a rebrand that is aimed at repositioning themselves in the minds of consumers. However, brands within safety sensitive industries must weigh the costs and risks of rebranding to determine whether these changes will have a lasting positive effect on the perception of their brand image. Considering this, the researcher aimed to determine whether KIA’s recent rebrand has affected the way in which consumers perceive the brand’s image. To accurately determine this, both demographic - and 19 five-point Likert scale questions where distributed in the form of a survey to quantitatively gather the necessary objective data. All questions within the survey were derived from Kapferer’s (2008) Brand Identity Prism and were measurable through descriptive and inferential statistics to ensure that the data was deemed fit for this research. Ultimately, the three sections being measured were focused on self-image, reflection, and physique after KIA’s rebrand. Positive and significant relationships were found between each of these sections and the perceptions of consumers, therefore indicating a positive effect. This research illustrates the effect of rebranding in industries that have very few instances thereof and serves as an indication to other automotive brands what the potential effect of a rebrand within the South African context might be.
Keywords: Brand identity; Rebranding; Revolutionary rebranding